2017
DOI: 10.1080/87565641.2017.1404065
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making in children in the Hungry Donkey Test: A behavioral analysis

Abstract: This study analyzed choice behavior in the Hungry Donkey Task, with a focus on learning trajectories and the stability of preference, in 100 children of different ages (8-9, 10-11, 12-13, 14-15, and 16-17 years old). The results indicated that (a) learning occurred as the task progressed, (b) early adolescents performed poorly during the task, and (c) most of the participants did not reach the stability criterion during the task. The present study suggests that decision-making in children and adolescents varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Given the limited research in this area, our non-significant results should be interpreted with caution. Studies conducted in children of a similar age range using both the Hungry Donkey Test 63 and Iowa Gambling Test 64 have shown that DMA varies with age in a U-shaped curve. Younger children perform better in the task compared to early-adolescents, with performance becoming again better in late adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited research in this area, our non-significant results should be interpreted with caution. Studies conducted in children of a similar age range using both the Hungry Donkey Test 63 and Iowa Gambling Test 64 have shown that DMA varies with age in a U-shaped curve. Younger children perform better in the task compared to early-adolescents, with performance becoming again better in late adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the hungry donkey task operationalizing affective decision-making, which consisted of 60 trials instead of the original 200 trials may have been affected ( Crone and van der Molen, 2004 ). As demonstrated by Cortes-Patino et al (2017) in a sample aged 8–17 years, these extra trials may be crucial for children to really apprehend the reward contingencies associated with each door. In their study, only 36% of the sample reached choice-stability for advantageous doors by the 200th trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the oldest participants (13–15 years) the cool EFs inhibition, working-memory updating, and cognitive flexibility became distinguishable, and a three-factor model provided an improved fit. While the development of cool EF seems to follow a linear pattern ( Best and Miller, 2010 ), some findings suggest a more complicated trajectory for hot EF characterized by protracted development and by particular caveats (i.e., a performance dip) during adolescence, with adult-like task performance achieved around 17–18 years ( Hooper et al, 2004 ; Zelazo and Carlson, 2012 ; Tsermentseli and Poland, 2016 ; Cortes-Patino et al, 2017 ). A developmental cascade would suggest that the early improvement of more basal cool EF like inhibition may initiate the specification of increasingly hot EF and complex SR abilities including anger regulation and long-term planning abilities later on in middle childhood and adolescence ( Best and Miller, 2010 ; McAuley and White, 2011 ; Prencipe et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%